Being PAL: Uncertainty and Coping in r/PregnancyAfterLoss. Issue 7 (7th June 2022) - Dalton, Elizabeth D.; Gruber, Katie
ABSTRACT: Women who become pregnant again following miscarriage or stillbirth are in a particularly vulnerable position as they grapple with uncertainty about the current pregnancy's viability and outcomes. In this study, we examine the types of uncertainty that emerge in pregnancy after loss (PAL) and how women manage that uncertainty. Framed by the theory of communication and uncertainty management, we thematically analyzed threads ( N = 636) from the online discussion board Reddit, focusing on the specific subreddit community r/PregnancyAfterLoss. Themes of physiological, emotional, and social uncertainty dominated the PAL experiences of these online community members. Uncertainty management and coping strategies included direct information seeking, bracing, mantras, and accepting uncertainty as part of the PAL experience. Theoretical contributions of this study include an initial conceptualization of emotional uncertainty in health communication. In addition, we draw parallels between uncertainty in PAL and in illness and highlight the unique features of PAL that expand our understanding of uncertainty in health. Practical implications are drawn from members' expressed needs and uncertainty management practices, and provide direction for supporting women through the PAL experience.